The role of leadership and organizational learning in fostering high performance of tourism firms in Vietnam - Ngoc Khuong Mai; Thanh Tung Do (Cogent Business & Management, 2023)
This study extends prior work by developing a comprehensive framework examining how leadership and organizational learning facilitate the achievement of high performance in organizations. Following quantitative approach, this study used survey questionnaire to collect data from leaders in the tourism sector. SmartPLS was applied to perform PLS-SEM statistical techniques with 638 responses collected. The findings revealed that high performance of tourism firms was directly and indirectly affected by leadership traits, leadership competencies, complexity leadership and organizational learning. This study has a significant contribution to leadership, organizational learning, and organizational high performance literature by providing a comprehensive framework of the relationships among these phenomena. Significant implications for both theory and practice were provided.
Keywords: 650; complexity leadership; leadership competence; leadership trait; Organizational high performance; organizational learning